Exploring Educotourism Through Eco-Literacy in English Learning Materials in MTs Sumber Bungur - Muqoddas, Najwa; Mulyadi (Institut Agama Islam Negeri Madura, 2023)
Some external factors affect the education system on the macro, including ideology, economy, politics, socio-culture, and natural environment. These factors affect each other in the educational system, including the interaction with the social and natural environment in the broader ecosystem. Eco-literacy should become the curriculum's main focus to face severe environmental problems in the future. The students' ecological intelligence can be grown through understanding the environment and how to be environmentally friendly. This study aims to investigate eco-literacy through English learning materials in terms of educotourism. This research applied the qualitative research method. The data showed in descriptive method because it needed to describe the eco-literacy in English learning materials in MTs Sumber Bungur Pakong regarding educotourism. Meanwhile, the data was collected from observations, interviews, and documentation in MTs Sumber Bungur Pakong. The research results showed the implementation of educotourism through eco-literacy in English earning materials in MTs Sumber Bungur Pakong by founding a syllabus design called ATP related to eco-literacy made by the school of MTs Sumber Bungur Pakong. The syllabus design existed two materials attached to eco-literacy are learned: obligations, prohibitions, and suggestions. Besides, the researcher also found the advantages and disadvantages in making the students aware of keeping the environment